The effectiveness of using interactive harmonic exercises in improving the level of some physical and motor abilities and intelligence for students aged (9-10) years - Salman , Thaer; Taha , Ruaa (Journal of Physical Education, 2024)
We discussed the proper preparation, directing, and implementation of physical education lessons, and clarification of the duties that fall upon the physical education teacher in addition to his physical and skill duties, which is the duty of the physical education lesson. The problem of the research lies in the fact that interactive harmonic exercises are not implemented accurately by physical education teachers because they require great experience, exceptional efforts, and accuracy in performance. The research aims to identify the level of some physical and motor abilities and intelligence among students aged (9-10) years, and to know the effect of some harmonic exercises. Interactivity at the level of some physical and motor abilities and the level of intelligence among students aged (9-10) years. As for the research hypotheses, they are that there are no statistically significant differences between the pre- and post-tests of the control and experimental groups in some physical and motor abilities and intelligence among students aged (9-10) years, and the absence of statistically significant differences in the post-tests between the control and experimental groups in some physical and motor abilities and intelligence among students aged (9-10) years. . The experimental approach was used, and the research population was identified with the students of the Lebanon Mixed Primary School of the Second Rusafa Education Directorate in Baghdad Governorate for the academic year 2023-2024 AD, aged (9-10) years, numbering (30) students. They were divided into a control group, numbering (15) students, and an experimental group, numbering (15) students. (6) students were identified as a sample for the exploratory experiment, and the study was applied. (5) tests to measure physical and motor abilities and one test to measure the level of intelligence. After processing and discussing the data, the researchers concluded that the use of interactive harmonious exercises within a physical education lesson has a positive impact on the variables of the study, as the results showed that there were statistically significant differences between the pre- and post-measurements of the experimental group and in favor of the post-measurement in all tests of physical and motor abilities and in the intelligence level of the students, and that the use of traditional teaching methods showed the presence of There were statistically significant differences between the pre- and post-measurements of the control group in all variables of the study except for the two tests (successive jumps in place for 10 seconds, and the Raven’s intelligence test), which indicates the presence of some kind of defect and shortcomings in some components of the traditional teaching curriculum.